Pendampingan Pembuatan Video Profil Sekolah Sebagai Media Promosi SMA Negeri 1 Palembang - Kanada, Rabial; Arwan, Arwan; Ibrahim, Ibrahim; Sakinah, Nazara Syifa; Imelda, Ovi; Meilinda, Nina (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
In today's digital era, audiovisual-based promotional media has become a strategic means of building the image and appeal of institutions, including educational institutions. SMA Negeri 1 Palembang, as one of the leading schools, needs to utilize digital media to convey information in a more engaging, interactive way and reach a wider audience. A school profile video is an effective communication tool to introduce the school's identity, vision and mission, achievements, and facilities to the broader public. The assistance process was carried out through several stages, including planning, production, and video editing, involving both students and educators. The method used in the Assistance Program for Creating a School Profile Video as a Promotional Medium at SMA Negeri 1 Palembang included observation and needs analysis, planning the assistance program, implementation, and identifying the expected outcomes. The results of the assistance showed that the process had a positive impact, both in enhancing students' technical skills in digital media production and in strengthening the school’s image as an excellent and competitive educational institution. The resulting profile video has proven to be an effective promotional medium in attracting prospective students and introducing SMA Negeri 1 Palembang to the broader community. Therefore, this assistance contributed to the development of the school’s digital media-based marketing strategy.ABSTRAKDi era digital saat ini, media promosi berbasis audiovisual menjadi sarana strategis dalam membangun citra dan daya tarik suatu lembaga, termasuk lembaga pendidikan. SMA Negeri 1 Palembang sebagai salah satu sekolah unggulan, perlu memanfaatkan media digital untuk menyampaikan informasi secara lebih menarik, interaktif, dan menjangkau khalayak luas. Video profil merupakan alat komunikasi yang efektif untuk memperkenalkan identitas, visi-misi, prestasi, serta fasilitas sekolah kepada masyarakat luas. Pendampingan dilakukan melalui beberapa tahapan, yaitu perencanaan, produksi, hingga penyuntingan video dengan melibatkan siswa dan tenaga pendidik. Metode yang digunakan dalam Pendampingan Pembuatan Video Profil Sekolah Sebagai Media Promosi di SMA Negeri 1 Palembang dengan tahapan observasi dan analisis kebutuhan, perencanaan program pendampingan, implementasi pendampingan dan luaran yang diharapkan. Hasil pendampingan menunjukkan bahwa proses pendampingan memberikan dampak positif, baik dalam meningkatkan keterampilan teknis siswa dalam produksi media digital maupun dalam memperkuat citra sekolah sebagai institusi pendidikan yang unggul dan berdaya saing. Video profil yang dihasilkan menjadi media promosi yang efektif dalam menarik calon siswa baru dan memperkenalkan SMA Negeri 1 Palembang kepada masyarakat luas. Dengan demikian, pendampingan ini berkontribusi dalam pengembangan strategi pemasaran sekolah berbasis media digital.